A peer-to-peer approach to energy production. (August 2015) - Giotitsas, Chris; Pazaitis, Alex; Kostakis, Vasilis
Abstract: This paper strives to provide a theoretical study for energy production and distribution. We thus examine and discuss the evolution of energy systems technologies and their impact on the global socio-economic structure. We critically analyze the evolution of the energy production infrastructure and then review the renewable and decentralized energy production technologies, while focusing on the concept of microgrids. Ultimately, we propose an alternative model, inspired by the commons-oriented practices, currently observed in the production of information, that utilizes microgrids in order to create a peer-to-peer energy grid and then discuss the conditions necessary for the "energy commons" to emerge. Highlights: This article provides a theoretical study for energy production and distribution. The evolution of the energy production infrastructure is discussed. We address the impact of the energy infrastructure on the socio-economic structure. We propose an alternative, commons-oriented energy production model.